PENGARUH PEMBERIAN KOMPOS TANDAN KOSONG KELAPA SAWIT(TKKS) TERHADAP PERKEMBANGAN CACING TANAH PADA PIRINGAN TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) - Purba, Kevin Arigi; Wawan, Wawan; Yulia, Arnis En (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
ABSTRACT               Palm oil (Elaeis guineensis Jacq.) Is one type of plantation that occupies the most important position in the agricultural sector, this is because oil palm is able to produce the largest economic value per hectare compared to other oil-producing or fat plants. Indonesia has a great opportunity to develop oil palm plantations, one of the provinces that is the center of oil palm development in Indonesia is Riau province. The positive impact of oil palm expansion besides being able to increase people's income, also expanding employment, while the negative impact caused damage to the properties of the land. This study aims to obtain the right dosage of OPEFB to breed worms and improve infiltration in inceptisol soil. This research was conducted at the Experimental Garden of the Faculty of Agriculture, University of Riau. This study was conducted experimentally using a completely randomized design (CRD) consisting of four treatments and four replications to obtain 16 experimental units. The factor used was 4 doses of OPEFB compost. The treatment of 430 g per 900 cm² was the best treatment for the development of earthworms as indicated by the highest number of tillers, number of cocoons, total earthworm weight and rate of soil infiltration Keywords: Palm oil plants, oil palm empty bunches, earthworms